The Impact of the COVID 19 Pandemic on the Health and Wellbeing of Aviation Workers Employed by Irish Registered Airlines. - Cahill, Joan (My University, 2022)
This study reports on the findings of an anonymous online survey (n=1,010) undertaken between October and December 2021 addressing the impact of the COVID 19 pandemic on the health and wellbeing of aviation workers, including those employed by Irish registered airlines. The survey incorporated several standardised instruments measuring levels of common mental health issues. Survey analysis indicates that a significant number of aviation workers are suffering from the symptoms of depression and anxiety. The prevalence of psychological anguish for aviation workers is higher than what is reported in the general population. Logistic regression was used to assess the probability of certain health outcomes for two groups – namely, participants working for Irish registered airlines and all other participants. The outcomes included reaching the threshold for clinical levels of depression and anxiety, suicidal ideation, and a life satisfaction/happiness rating greater or equal to the population average reported by the Organisation for Economic Co-operation (OECD). Statistical analysis indicates that the probability of having major depression and anxiety is higher for those working for Irish registered airlines. Employees of Irish registered airlines are less likely to rate their life satisfaction and happiness level the same or above the OECD average, as compared with all others. However, statistical analysis indicates that working for an Irish registered airline does not either increase or decrease the probability of suicidal ideation. Given that wellbeing is a factor in safe performance, aviation organisations need to develop new approaches to integrating wellbeing and safety culture, and associated safety management processes.
European Safety and Reliability Conference (ESREL) 2022
ACCEPTED
http://hdl.handle.net/2262/101056
Dublin
Keywords: COVID; Mental Health; Aviation Workers; Safety; Wellbeing; Culture; Inclusive Society; Aviation Human Factors; Aviation Safety; COVID 19 Pandemic; MENTAL HEALTH; Occupational Health and Safety; Mental Health/Psychosocial disability; Culture; Employment; Health